PRAGMATIC STUDY OF THE CATEGORY OF RELATION: THE FORMULATION OF THE PROBLEM (International Congress on Economics, Management and Business Studies, 2026)
In this article studying necessity of pragmatic aspect of ratio category forms is analyzed. The views relating to this matter are critically studied. The author conception concerning studying of ratio pragmatics is narrated.
Keywords: ratio, category, pragmatics, semantics, speech act.